Respostas

A melhor resposta!
2014-03-22T15:13:16-03:00
A)X-2(x+1)=-2X+7
x-2x-2= -2x +7
x=9
S={9)

b)(x+3).(x-2)=0
x² -2x +3x -6=0
x² +x -6=
Delta: b²-4.a.c --> 1²- 4.1.(-6)= 1+24= 25
Baskara:
(-b +/-Vdelta)/2.a -->
 x1= (-1 + 5)/ 2= 4/2 = 2
x2= (-1-5)/2 = -6/2 = -3
S={ -3, 2)

c)3.(2x-1)²-(2x+1).(2X-1)=2x+1
(6x-3)² -(4x²-2x +2x -1)= 2x +1
(36x² -36x +3² ) (-4x²+2x -2x +1)= 2x +1
(36x² -36x +9) -4x² - 2x = 0
32x²- 38x +9=0
Delta: 1444- 4.32.9=  1444-1152= 292
(38 +/- 2V73)/64
x1= (19 + V73)/32
x2= (19-V73) /32
S=( 19 +V73)/32, (19- V73)/32 )
             

1 5 1